Exploiting Focused Ultrasound to Aid Intranasal Drug Delivery for Brain Therapy - Barbato, Gaetano; Nisticò, Robert; Triaca, Viviana (Frontiers in Pharmacology, 2022)
Novel effective therapeutic strategies are needed to treat brain neurodegenerative diseases and to improve the quality of life of patients affected by Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), Amyotrophic Lateral sclerosis (ALS), as well as other brain conditions. At present no effective treatment options are available; current therapeutics for neurodegenerative diseases (NDs) improve cognitive symptoms only transiently and in a minor number of patients. Further, most of the amyloid-based phase 3 clinical trials recently failed in AD, in spite of promising preclinical and phase 1-2 clinical trials, further pinpointing the need for a better knowledge of the early mechanisms of disease as well as of more effective routes of drug administration. In fact, beyond common pathological events and molecular substrates, each of these diseases preferentially affect defined subpopulations of neurons in specific neuronal circuits (selective neuronal vulnerability), leading to the typical age-related clinical profile. In this perspective, key to successful drug discovery is a robust and reproducible biological validation of potential new molecular targets together with a concomitant set up of protocols/tools for efficient and targeted brain delivery to a specific area of interest. Here we propose and discuss Focused UltraSound aided drug administration as a specific and novel technical approach to achieve optimal concentration of the drug at the target area of interest. We will focus on drug delivery to the brain through the nasal route coupled to FUS as a promising approach to achieve neuroprotection and rescue of cognitive decline in several NDs.